Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1159/000215735
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Maturing Perineal Lipoblastoma in an Infant

Abstract: Objective: To report the unusual occurrence of a perineal lipoblastoma presenting as a painless enlarging mass in an infant. Case Presentation and Intervention: A 7-month-old boy presented with a 6-month history of an asymptomatic progressively enlarging perineal mass. Imaging studies were unable to provide a diagnosis. Complete resection of the mass was achieved and there was no recurrence at 18-month follow-up. Histopathologic findings were consistent with a maturing perineal lipoblastoma. Conclusion: This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Ultrasonography, computed tomography (CT), and magnetic resonance imaging (MRI) complement each other, but seldom can they determine whether the tumor is benign or malignant. [17] Our patient was admitted to the operating theater based on his clinical picture, physical examination, and CT findings, but the histopathologic and cytogenetic studies established the diagnosis. Lipoblastoma has prominent lobulation, no nuclear atypia, or pleomorphism.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Ultrasonography, computed tomography (CT), and magnetic resonance imaging (MRI) complement each other, but seldom can they determine whether the tumor is benign or malignant. [17] Our patient was admitted to the operating theater based on his clinical picture, physical examination, and CT findings, but the histopathologic and cytogenetic studies established the diagnosis. Lipoblastoma has prominent lobulation, no nuclear atypia, or pleomorphism.…”
Section: Discussionmentioning
confidence: 91%
“…No metastasis has been reported until today. [17] Complete surgical excision is curative with no recurrence. In histologically borderline cases, the tumor karyotype is of diagnostic value in order to differentiate with liposarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…1 In our present study, FB and food bolus impactions were found in 242 and 11 patients, respectively, out of 368 patients (68.75%), which differs from western studies that reported FBs in the range of 80%. 2 17 18 19 20 21 This inconsistency could be related to delay in referral from the outlying hospitals for endoscopic procedure resulting in a high likelihood of spontaneous passage of FB through the digestive tract with time. Of the total 253 patients with FB ingestion in our study, 67% were aged less than 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Also, emergency endoscopic retrieval was undertaken in those presenting with symptoms of complete esophageal obstruction or dyspnea and those with sharp pointed objects in the upper digestive tract in accordance with other studies. 3 21 Patients with BBs and other FBs (except sharp objects) in the stomach were subjected to endoscopy on an average of 6.2 hours from the time of their arrival to the ED (range: 2–8 hours).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation